FV HR2 Haplotype as Additional Inherited Risk Factor for Deep Vein Thrombosis in Individuals with a High-Risk Profile - Margaglione, Maurizio; Bossone, Anna; Coalizzo, Donatella; D’Andrea, Giovanna; Brancaccio, Vincenzo; Ciampa, Antonio; Grandone, Elvira; Di Minno, Giovanni (Thrombosis and Haemostasis, 2002)
A number of strongly linked polymorphisms within the Factor V gene (FV HR2 haplotype) has been identified as a cause of resistance to activated protein C, and has suggested a modest risk factor for vein thrombosis. We investigated the frequency of the HR2 haplotype in 433 consecutive patients with confirmed deep vein thrombosis and 326 controls. The HR2 haplotype was more frequent in patients (15.2%) than in controls (10.1%). The risk of thrombosis among carriers of this haplotype was significantly increased (odds ratio: 1.6 [95% CI: 1.0-2.5]). The estimated risk associated with the HR2 haplotype was 1.8 (95% CI: 1.1-2.9) in subjects with (n = 255), and 1.4 (95% CI: 0.8-2.4) in those without (n = 178) acquired risk factors for vein thrombosis. After adjustment for sex, FV Leiden and FII A20210 mutations, the estimated risk of vein thrombosis among carriers of the HR2 haplotype was 1.8 (95% CI: 1.1-2.8). Present data indicate that the HR2 haplotype is independently associated with vein thrombosis among individuals with a highrisk profile.
Keywords: HR2 haplotype; FV gene; inherited risk factors; vein thrombosis